Pengaruh Work Life Balance dan Job Burnout Terhadap Employee Performance Dimoderasi oleh Employee Engagement pada Analis Laboratorium Wanita di Jabodetabek - Salsa Bila Rahayu; Jatmiko Jatmiko (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to analyze the influence ofwork-life balance And job burnout to employee performancemoderated byemployee engagementon female laboratory analysts in the Jabodetabek area. This study was based onsocial exchange theory, which explains that the interaction between employees and the organization is reciprocal, wherework life balanceand leveljob burnoutcan affectemployee performance. Data were collected through a survey using a questionnaire.onlinedistributed to 291 respondents. The analysis method used isStructural Equation Modeling(SEM) with LISREL software. The results of the study showed thatjob burnouthave a negative influence onemployee performance, whereas organizational supportnegatively affectjob burnout. However, work-life balancedoes not have a significant effect onjob burnoutand alsoemployee performance. Besides that, employee engagementproven to strengthen the negative relationship betweenjob burnout And employee performance. This finding indicates thatwork life balancedoes not always contribute to improvementemployee performance. On the other hand, the leveljob burnouthigh can decreaseemployee performance, especially in employees with high involvement in their work. Organizational support has been shown to be an important factor in reducingjob burnoutand maintain employee motivation and productivity. The implications of this study can be used by companies in developing human resource management strategies to improveemployee performancethrough improvementemployee engagementand better organizational support.